Two Decades of STEM Education Research in Middle School: A Bibliometrics Analysis in Scopus Database (2000-2020) - Huong Le Thi Thu; Trung Tran; Thao Trinh Thi Phuong; Trinh Le Thi Tuyet; Hoang Le Huy; Thuy Vu Thi (MDPI AG, 2021)
STEM education has become important in many countries around the world. STEM education can begin while students are very young. However, earlier research has shown that one of the most important factors influencing the decision on scientific research selection is the middle school science classes. In this research, we extract database from Scopus to evaluate the scientific results of publications in the field of STEM education in middle school in the period 2000-2020. A data set of 272 academic papers was indexed to monitor the development of this field by Scopus. The results of the quantitative analysis showed that researches on STEM education in middle schools have boomed in the last 5 years, mainly in the USA. The trend of research collaboration in the field of STEM education in middle schools is not strong. The research topics are quite diverse, focusing on a number of issues: gender, engineering education, curriculum, etc. This study has some limitations, including that only data from the Scopus database were selected and manually filtered, so our analyses totally depended on the quality of the input information imported from the Scopus database.